PPARγ is critical for Mycobacterium tuberculosis induction of Mcl-1 and limitation of human macrophage apoptosis. - Eusondia Arnett; Ashlee M Weaver; Kiersten C Woodyard; Maria J Montoya; Michael Li; Ky V Hoang; Andrew Hayhurst; Abul K Azad; Larry S Schlesinger (PLoS Pathogens)
Peroxisome proliferator-activated receptor (PPAR)γ is a global transcriptional regulator associated with anti-inflammatory actions. It is highly expressed in alveolar macrophages (AMs), which are unable to clear the intracellular pathogen Mycobacterium tuberculosis (M.tb). Although M.tb infection induces PPARγ in human macrophages, which contributes to M.tb growth, the mechanisms underlying this are largely unknown. We undertook NanoString gene expression analysis to identify novel PPARγ effectors that condition macrophages to be more susceptible to M.tb infection. This revealed several genes that are differentially regulated in response to PPARγ silencing during M.tb infection, including the Bcl-2 family members Bax (pro-apoptotic) and Mcl-1 (pro-survival). Apoptosis is an important defense mechanism that prevents the growth of intracellular microbes, including M.tb, but is limited by virulent M.tb. This suggested that M.tb differentially regulates Mcl-1 and Bax expression through PPARγ to limit apoptosis. In support of this, gene and protein expression analysis revealed that Mcl-1 expression is driven by PPARγ during M.tb infection in human macrophages. Further, 15-lipoxygenase (15-LOX) is critical for PPARγ activity and Mcl-1 expression. We also determined that PPARγ and 15-LOX regulate macrophage apoptosis during M.tb infection, and that pre-clinical therapeutics that inhibit Mcl-1 activity significantly limit M.tb intracellular growth in both human macrophages and an in vitro TB granuloma model. In conclusion, identification of the novel PPARγ effector Mcl-1 has determined PPARγ and 15-LOX are critical regulators of apoptosis during M.tb infection and new potential targets for host-directed therapy for M.tb.